A Malthusian-Frontier Interpretation of United States Demographic History Before c. 1815 - Smith, Daniel (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
The combination of a three per cent rate of population growth and an absence of per capita economic growth was fundamental to the history of the British colonies in North America and the early United States. These characteristics sharply differed from the economy and demography of the nineteenth century United States and from the experience of other societies. These distinctive features had significant consequences; the "Malthusian-frontier" regime helps to explain the extremely slow pace of urbanization, the stability in the inequality of wealth, and the pattern of conflict and elite domination in politics. Although rapid natural increase created economic, social, and political difficulties, migration toward the frontier served to equilibrate the system. Using data from late eighteenth century New England towns, the paper demonstrates how migration tended to act as a homeostatic mechanism but also argues that out-migrants from more densely-settled areas were pushed rather than pulled. Several factors account for the "stickiness" of the migration process. Throughout, the essay illustrates the utility of a systemic approach to demographic history.